Regulatory Effect of Inflammatory Mediators in Intervertebral Disc Degeneration - Li, Zhangfu; Yang, Honghao; Hai, Yong; Cheng, Yunzhong (Mediators of Inflammation, 2023)
Intervertebral disc degeneration (IDD) is a major contributor to back, neck, and radicular pain. It is related to changes in tissue structure and function, including the breakdown of the extracellular matrix (ECM), aging, apoptosis of the nucleus pulposus, and biomechanical tissue impairment. Recently, an increasing number of studies have demonstrated that inflammatory mediators play a crucial role in IDD, and they are being explored as potential treatment targets for IDD and associated disorders. For example, interleukins (IL), tumour necrosis factor-α (TNF-α), chemokines, and inflammasomes have all been linked to the pathophysiology of IDD. These inflammatory mediators are found in high concentrations in intervertebral disc (IVD) tissues and cells and are associated with the severity of LBP and IDD. It is feasible to reduce the production of these proinflammatory mediators and develop a novel therapy for IDD, which will be a hotspot of future research. In this review, the effects of inflammatory mediators in IDD were described.